Interruption of the distal left pulmonary artery with pulmonary arteriovenous fistulas and atrial septal defect - Günal, Nazlıhan; Bilgiç, Arman; Alehan, Dursun; Lenk, Mustafa Koray (The Turkish Journal of Pediatrics, 1997)
A seven-year-old boy with interrupted left pulmonary artery, arteriovenous fistulas and atrial septal defect is presented. The anomalies were identified by echocardiography and angiography. On pulmonary artery angiograms, left pulmonary artery discontinuity (as though the distal segment had been interrupted), diffuse granular opacification of right lung fields, and early visibility of the left atrium were observed.